The Effect of Perceived Usefulness and Perceived Easy to Use on Student Satisfaction The Mediating Role of Attitude to Use Online Learning - Nuryakin Nuryakin; Nandrianina Louis Pierre Rakotoarizaka; Hussein Gibreel Musa (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
The aims of this study is to analyze an empirical research model on the effect of perceived usefulness and perceived ease to use on student satisfaction with the mediating role of attitude to use online learning. The sample of this study were students from the Faculty of Economics and Business, Yogyakarta Muhammadiyah University. An empirical model and hypothesis testing was analyze using the Structural Equation Modeling (SEM) of the AMOS 23 program. The design of this study uses a quantitative approach. A sample of 203 students were tested in this study. The sampling technique used purposive sampling. The results of hypothesis testing show that there is a positive and significant effect between perceived usefulness and satisfaction and attitude. Perceived easy to use has a significant positive effect on attitude to use online learning but not significant on student satisfaction. Attitude to use online learning has a significant positive effect on student satisfaction.